Influence of Environmental Risks on the Feasibility of Household Sanitation in Purworejo Regency, Central Java Analysis of Geographic Location, Income, and Education Level - Vicera Romindo Toga Torop (PT Mattawang Mediatama Solution, 2024)
This study examines the factors that influence the feasibility of household sanitation in Purworejo Regency, Central Java. The research utilizes survey data from Indonesia's National Socio-Economic Survey (SUSENAS) that includes 785 households in Purworejo Regency from March 2022. The results reveal that 23.3% of households in the region do not have suitable sanitation facilities. The findings show that location, particularly in rural areas, income level, and the level of education attained by the household head significantly impact the availability of appropriate sanitation. Households located in rural zones and those with lower incomes or heads of household with lower education levels are at greater risk of lacking suitable sanitation. The conclusions suggest that improvements to income and education, as well as infrastructure development in rural settings, can help boost access to appropriate sanitation.